The Development of the Sugarcane Industry to Enhance Production Cost Efficiency in Sungai Asam Kayu Aro Village, Kerinci Regency - Abdallah, Zachari; Putri, Nurapni Jami; Maryanto, Maryanto (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The sugarcane palm sugar industry is a strategic plantation sector in Kerinci Regency, particularly in Sungai Asam Village, where approximately 95% of the population has depended on this commodity for generations. However, this home-based industry faces serious challenges, including a decline in the number of business units due to highly traditional cultivation methods, the continued use of non-uniform local seedlings originating from the colonial era, and the absence of standardized post-harvest management practices. This community service activity aims to document the profile of existing local sugarcane cultivation and to identify solutions to low productivity, which currently averages only about 6 tons per hectare. The implementation method involved farmer surveys using a snowball sampling technique and field observations on 10 × 10 meter sample plots. The results indicate that by applying a selective harvesting method on a 1-hectare plantation, farmers are able to produce an average of 200 kg of palm sugar per week, with an average yield recovery rate of 12.07%. The resulting income reaches approximately IDR 4,000,000 per month, which is economically higher than income from oil palm land management. It can be concluded that the sugarcane palm sugar business in Sungai Asam Village has strong economic prospects; however, it requires interventions such as the adoption of superior varieties, improvements in farmers’ cash flow financing systems, and diversification of processed products to enhance market value and boost the regional economy.